PERUBAHAN POLITIK OLEH FAKTOR AGAMA - Budi Pramono (POLITIK, 2017)
The Islamic revolution in Iran in 1979 was a unique process of political changes in all over the world. The autocratic state led by the Pahlavi dynasty was transformed into a state that made religious values as the basis of state administration. Thus, this writing will discuss about the chronology of Islamic revolution started since Reza Pahlavi era up to the establishment of an Islamic state. By using descriptive analysis, to deepen the political changes, the writer will use the component of political system in political changes context by Huntington, furthermore, the criteria of political developments by Almond and Powell — The political system component in Iran did not support the continued maintenance of the Pahlavi dynasty regime. It can be clearly seen there was no such a thing like political developments but the collapse of the regime.Keywords: The revolution in Iran, political changes, religionRevolusi Islam di Iran pada 1979, merupakan sebuah proses perubahan politik yang unik di dunia. Negara otokratik yang dipimpin oleh dinasti Pahlavi mengalami perubahan menjadi negara yang menjadikan nilai agama sebagai dasar penyelenggaraan negara. Tulisan ini akan membahas revolusi Islam secara kronologis dimulai dari sejak berkuasanya Reza Pahlavi sampai dengan pembentukan negara Islam. Dengan menggunakan deskriptif analisis, sementara, untuk mendalami perubahan politik akan digunakan komponen sistem politik dalam konteks perubahan politik seperti yang diajukan Huntington, serta, kriteria perkembangan politik yang diajukan oleh Almond dan Powell — lewat itu akan tampak dengan jelas, ternyata, komponen dalam sistem politik di Iran tidak tidak mendukung tetap terjaganya keberlangsungan rezim dinasti Pahlavi. Hal tersebut tampak dengan jelas, tidak terjadinya perkembangan politik menuju sistem yang lebih baik, telah mendorong kepada kejatuhan rezim.